EVALUATION OF ANTIPEROXIDATIVE POTENTIAL OF WATER EXTRACT OF SPIRULINA PLATENSIS ON BUSULFAN-INDUCED LIPID PEROXIDATION USING 4-HYDROXY NONENAL AND NITRIC OXIDE AS MODEL MARKERS: Pharmaceutical Science-Pharmaceutical Chemistry - RAY, SUPRATIM (International Journal of Life Science and Pharma Research, 2011)
This in vitro study was designed to evaluate free radical scavenging activity of water extract of Spirulina platensis on busulfan-induced lipid peroxidation using 4-hydroxy nonenal and nitric oxide as model markers. In this study goat liver has been used as liver source. The results suggest that busulfan could induce lipid peroxidation to a significant extent and it was also found that water extract of the Spirulina platensis has the ability to suppress the busulfan-induced toxicity.